Federal Economic Measures to Combat the Pandemic Crisis and the Federative Pact (Global Journal of Human-Social Science, 2025)
This article seeks to explain the economic measures adopted by the Federal Government in response to the pandemic caused by the novel Coronavirus COVID-19 Constitutional Amendment No 106 and Complementary Law No 173 will be used as a reference basis with the aim of demonstrating how the fiscal regime was changed within the constitutional possibilities to maintain the country s economic health and how the states were impacted by the actions of the Federal Government This study will analyze the changes in budgetary and fiscal rules and the distribution of resources among the states as a way of compensating for the loss of tax revenue From another perspective spending containment assumes an important role in combating the crisis and economic recovery is now being discussed in actions such as the suspension of states debts with the Union Ultimately the distribution of resources allocated for this purpose from the perspective of the federative pact and how balance should be maintained on its basis should be determined The theoretical framework is provided through specialized doctrines scientific articles specific legislation and the qualitative and descriptive approach
Keywords: financial assistance; health crisis; revenue sharing; federative pact